Effects of functional diversity on ecosystem services in cocoa agroforestry systems in Costa Rica - Cassio Pinheiro Edelstein; Marney E. Isaac; Marney E. Isaac; Luis Orozco-Aguilar; Felipe Peguero; Felipe Peguero; Diego Delgado-Rodríguez; Rolando H. Cerda (Frontiers in Sustainable Food Systems)
Cocoa agroforestry systems (AFS) provide multiple ecosystem services, which are influenced by features of the shade tree community. By strategically selecting and managing shade trees based on their functional traits, cocoa farmers can affect functional diversity of AFS and potentially enhance the benefits they deliver. In this research, we applied functional trait ecology to better understand the effect of functional diversity of cocoa AFS on three ecosystem services: carbon storage, soil fertility, and provisioning of cocoa and other products. To achieve this, we characterized 30 AFS across a gradient of ecological complexity and established relationships between functional diversityw indices and ecosystem services using ANOVA and multiple regression models. As a result, two contrasting ecological dynamics were observed: low-complexity AFS, dominated by resource-conservative traits (higher leaf dry matter content, higher stem specific density, and low leaf nitrogen concentration), were associated with lower carbon stocks and soil fertility, while high-complexity AFS, characterized by resource-acquisitive traits (low leaf dry matter content, low stem specific density, and high leaf nitrogen concentration), delivered greater ecosystem services. Through the multiple regression analysis, we found that AFS dominated by species with greater maximum potential height, greater leaf nitrogen concentration, lower leaf dry matter content, lower leaf mass per area, and lower leaf nitrogen-phosphorus ratio were associated with higher carbon storage (R2 = 0.84), soil fertility (R2 = 0.7 for soil nitrogen), and multiple ecosystem services (R2 = 0.78). Additionally, cocoa yields were negatively correlated with shade cover and the dominance of large-leaf shade trees, revealing a potential trade-off between maximizing yields and enhancing ecosystem services. Nevertheless, the models indicated that a win-win scenario can be achieved when shade trees are productive, generating additional benefits. Finally, our study highlights critical relationships between shade tree traits and delivery of key ecosystem services for farm sustainability and farmer livelihoods.